2017
DOI: 10.1016/j.compstruct.2017.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Bend-strength of novel filament wound shear reinforcement

Abstract: The winding of Fibre Reinforced Polymer (FRP) tows around longitudinal reinforcing bars provides a novel method for the fabrication of reinforcement cages for concrete structures. A key limitation on the contribution of FRP to the shear capacity of a concrete member is found at corners, where stress concentrations can lead to premature failure. An experimental programme, comprising 30 test samples, was undertaken to assess the bend capacity of filament wound FRP (W-FRP) shear links manufactured using a carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 13 publications
1
32
0
Order By: Relevance
“…The limit stress value was then quantified by multiplying the observed maximum strain by the Young's modulus of the CFRP wrap. To account for the reduction in strength of the CFRP wrap at its bent corners, the above limit stress was multiplied by a corner efficiency factor of 0.4 as suggested by others [30,31]. The stress distributions of Figure 12 show for the two cases analyzed a concentration of stresses at the bottom corner of the GFRP angle, corroborating the experimentally observed initial cracking starting at this location.…”
Section: Numerical Simulationssupporting
confidence: 68%
“…The limit stress value was then quantified by multiplying the observed maximum strain by the Young's modulus of the CFRP wrap. To account for the reduction in strength of the CFRP wrap at its bent corners, the above limit stress was multiplied by a corner efficiency factor of 0.4 as suggested by others [30,31]. The stress distributions of Figure 12 show for the two cases analyzed a concentration of stresses at the bottom corner of the GFRP angle, corroborating the experimentally observed initial cracking starting at this location.…”
Section: Numerical Simulationssupporting
confidence: 68%
“…Composite sandwich structures are highly suitable for applications as structural components that require low-mass and flexibly, such as in aerospace, marine, and civil engineering fields [1]. The composite sandwich structure consists of two thin but stiff composite skins separated by a light-weight core [2].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, with the aid of computer automatic control and 3D printing, various shaped FRP reinforcements (shown in Figure 10) are currently available on the construction market. An advanced filament winding manufacturing process has been developed, in which resin-impregnated fibers are wound onto specially-designed mandrels to produce customized closed shapes such as shear stirrups [55,99]. In these pre-bent closed loop stirrups, the material is wound around a mold into one large stirrup.…”
Section: Prefabricated Frp Composites and Future Challengesmentioning
confidence: 99%
“…This becomes an issue in curved FRP reinforcements in RC structures, since premature failures can occur at the bent corner, as reported in the existing literature [33,43,[53][54][55][56]. Indeed, the results from such research studies have shown that the tensile strength of a bent portion of an FRP bar can be as low as 25% of the maximum tensile strength of that developed in the straight part.…”
Section: Introductionmentioning
confidence: 99%